2012
DOI: 10.1159/000338185
|View full text |Cite
|
Sign up to set email alerts
|

CSF Biomarkers Correlate with Cerebral Blood Flow on SPECT in Healthy Elderly

Abstract: Background: The preclinical patterns of biological markers for Alzheimer’s disease (AD) in vivo need further exploration. The aim of this study was therefore to investigate CSF biomarkers, regional cerebral blood flow (rCBF) and cognitive performance in cognitively healthy older individuals. Method: Within a 2-week period, 32 cognitively healthy older individuals underwent CSF analysis, rCBF measurement and cognitive testing. The CSF was analysed for β-amyloid1–42 (Aβ42), total tau protein (T-tau) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…Furthermore, the results of the present study showed thatthe presence of OH in patients with DM was independently associated with elevated T-tau and P-T181-tau levels in neural-derived plasma exosomes. In line with previous studies performed in normal cognition, reductions in cerebral blood ow were associated with increased cerebrospinal uid total tau and phosphorylated tau [28,29]. There are several pathways through which cerebral hypoperfusion may contribute to increased levels of neuronal tau in the brain.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the results of the present study showed thatthe presence of OH in patients with DM was independently associated with elevated T-tau and P-T181-tau levels in neural-derived plasma exosomes. In line with previous studies performed in normal cognition, reductions in cerebral blood ow were associated with increased cerebrospinal uid total tau and phosphorylated tau [28,29]. There are several pathways through which cerebral hypoperfusion may contribute to increased levels of neuronal tau in the brain.…”
Section: Discussionsupporting
confidence: 90%
“…They found out that the CSF level of p-tau correlated positively with rCBF in the left frontotemporal border zone area. They also realized a negative signi cant correlation between rCBF in the right superior posterior medial frontal lobe in healthy elderly (1). Similarly, our analysis shows a signi cant correlation between the plasma level of NFL and CBF changes in widespread areas of the brain between healthy subjects.…”
Section: Discussionsupporting
confidence: 80%
“…heretofore most studies emphasized the correlation between CSF level of biomarkers and regional cerebral blood ow changes in neurodegenerative diseases. For example, Stomrud et al investigated the correlation between CSF biomarkers and cerebral blood ow in healthy elderly (1). They found out that the CSF level of p-tau correlated positively with rCBF in the left frontotemporal border zone area.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal Aβ downregulation in the pre-AD CSF appears to be associated with the onset of temporoparietal CBF reduction and this hypoperfusion then worsens with the onset of abnormal CSF tau upregulation [12]. High CSF phospho-tau (p-tau) and total tau in the healthy brain have been correlated with reduced CBF in frontotemporal regions [76]. The elucidation of such stereotyped and progressive changes in pre-AD patients and through the course of the disease could aid in differential diagnosis at an early stage of disease progression and aid in preclinical prediction of disease risk, potentially allowing for early intervention.…”
Section: Cerebrovascular Alterations In Alzheimer’s Diseasementioning
confidence: 99%